Migrating from traditional grid to smart grid in smart cities promoted in developing country. (June 2021) - Saidani Neffati, Omnia; Sengan, Sudhakar; Thangavelu, Kalavathi Devi; Dilip Kumar, Sharma; Setiawan, Roy; Elangovan, Mohanraj; Mani, Devi; Velayutham, Priya
Abstract: Smart Grid is a term that encompasses the economic benefits of an intelligent and advanced power grid to reach changing responsibilities related directly to sustainability and energy efficiency. Considering the shortfall of alternative fuels in developed regions, the new smart grids, in order to have access to their environmental hazard, show that the average non-renewable and renewable energy sources can be integrated to reduce environmental disasters to improve production costs significantly. In order to provide reliable, secured, and cost-effective power grid functions, infrastructures can quickly and effectively co-ordinate power-sharing between several renewable energy sources freely accessible and economically demand costs. This article reviews the conceptual model, goals, architecture, potential benefits, and power grid issues with a complete and accurate understanding of the different defenders and people involved in the worldwide region scenario. The article examined energy and transmission issues, including smart grids and grid barriers, comprehensively.